ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK - Sulastri Sulastri; Arivetullatif Arivetullatif; Nurhasnah Nurhasnah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The purpose of this study is to analyze the financial performance of PT Industri Jamu dan Farmasi Sido Muncul Tbk during the period 2021-2023 through financial ratio analysis. The ratios analyzed include liquidity ratios (Current Ratio and Quick Ratio), solvency ratios (Debt to Total Asset Ratio and Total Debt to Equity Ratio), activity ratios (Inventory Turnover and Total Assets Turnover), and profitability ratios (Return on Investment and Return on Equity). The research method used is descriptive quantitative with secondary data sources from the company's financial statements for the period 2021-2023 obtained from the official website of the Indonesia Stock Exchange (IDX). Data analysis is carried out using descriptive quantitative analysis through financial ratio analysis. Based on the results of calculating the financial ratio analysis for the period 2021-2023, the financial performance in terms of liquidity ratios is classified as good, with the ratio level above the industry standard. In the solvency ratio, finance performance is also classified as good, with the ratio level not exceeding the industry standard. In the activity ratios and profitability ratios, performance is not good enough, with low ratio levels still below the industry standard. Keywords : Financial Performance, Liquidity Ratio, Solvency Ratio, Activity Ratio, Profitability Ratio